2018
DOI: 10.1001/jamaoncol.2018.0264
|View full text |Cite
|
Sign up to set email alerts
|

Delays in the Publication of Important Clinical Trial Findings in Oncology

Abstract: Even for the most pressing study findings, median publication delays approach 1 year. As publication delays hinder research progress and advancements in clinical care, policies that enable early preprint release or public posting of completed data analysis should be pursued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
0
27
0
2
Order By: Relevance
“…the results of many clinical trials are never reported or only reported years after trial completion 123. Delays in publication can cause harm as scientists work without knowing what others have done or found 45. Moreover, for public health emergencies, when rapid communication is essential, preprint servers can immediately disseminate study findings globally, fostering scientific exchange 6…”
Section: Yes—harlan M Krumholz Joseph S Rossmentioning
confidence: 99%
“…the results of many clinical trials are never reported or only reported years after trial completion 123. Delays in publication can cause harm as scientists work without knowing what others have done or found 45. Moreover, for public health emergencies, when rapid communication is essential, preprint servers can immediately disseminate study findings globally, fostering scientific exchange 6…”
Section: Yes—harlan M Krumholz Joseph S Rossmentioning
confidence: 99%
“…This criticism of publication delays may be well-founded. For example, a recent study in JAMA Oncology found that results from phase III oncology trials have a median time to publication of 350 days and even longer if reporting negative findings [3]. While such delays may negatively affect patients, scientists may suffer as well.…”
Section: Introductionmentioning
confidence: 99%
“…This criticism of publication delays may be well-founded. For example, a recent study in JAMA Oncology found that results from Phase III oncology trials have a median time to publication of 350 days and even longer if reporting negative findings [3].…”
Section: What This Article Addsmentioning
confidence: 99%